Metaphors of Love in The Tortured Poets Department Album By Taylor Swift - Putu Dabrina Cintania Jaya; Putu Lirishati Soethama; Putu Weddha Savitri (Pusat riset dan Inovasi Nasional, 2025)
This study explores how love metaphors are expressed in three selected songs: Guilty as Sin, The Alchemy, and But Daddy I Love Him, from Taylor Swift's The Tortured Poets Department album. Language plays a crucial role in conveying abstract emotions like love, and metaphor is a powerful tool for articulating complex feelings in song lyrics. Using a qualitative-descriptive approach, the research analyzes the lyrics through Lakoff and Johnson’s conceptual metaphor theory, categorizing metaphors into structural, ontological, and orientational types. Data were collected by closely reading the lyrics and noting metaphorical expressions, which were then interpreted within their emotional and thematic contexts. The findings reveal that ontological and structural metaphors dominate, portraying love as poetic storytelling and an evolving emotional journey, while no orientational metaphors were identified. This study highlights how Taylor Swift employs metaphorical language to capture the multifaceted nature of love, heartbreak, and personal transformation, demonstrating the significant role of metaphor in shaping emotional meaning in contemporary popular music.